영상제작인력의 전문성과 경력장애가 이들의 직무만족에 미치는 영향 - 업무효능감의 매개효과와 성차별적 직장환경의 조절효과분석을 중심으로 - 이희진; Lee Hee Jin (여성학연구, 2018)
본 연구는 다양한 미디어 영역에서 영상제작의 증가로 영상제작인력의 중요성이 더욱 커지는 상황에서, 영상제작 종사자들을 대상으로, 이들의 직무만족에 전문성과 경력장애가 각각 직접적으로 미치는 영향과 함께, 업무효능감의 매개효과를 밝히고, 이러한 직·간접효과에 대한 성차별적 직무환경의 조절효과를 실증적으로 규명하는 데 그 목적을 두었다. 영상제작인력에 대한 관련 학계에서의 체계적인 연구가 이루어지지 않고 있음에 대해 문제제기를 하면서, 본 연구는 다양한 영역에(12개) 활동하고 있는 다양한 직급(4개)의 영상제작 종사자들을 대상(402명)으로 설문조사를 실시하여 얻은 자료를 토대로 분석한 실증연구이다. 연구모형에 설정한 직·간접경로를 분석은 구조방정식모형(SEM)을 토대로 AMOS 20을 사용하여 분석하였다. 부트스트레핑 방법을 사용하여 매개효과를 검증을 하였고, 다집단분석을 이용하여 조절효과를 분석하였다. 자료분석 결과를 요약하면 다음과 같다. 첫째, 직장에서 임금, 승진, 업무역할 등에서 성차별 수준이 높은 집단과 낮은 집단 모두 영상제작 종사자들의 직무만족에 이들의 전문성은 직접적으로 영향을 미치지 않았지만, 경력장애는 직무만족에 정적 직접효과를 미치는 것으로 밝혀졌다. 둘째, 두 집단 모두 업무효능감에 경력장애는 직접적인 효과를 미치지 않았지만, 전문성은 업무효능감에 정적 직접효과를 미쳤다. 셋째, 성차별이 낮은 집단에서는 업무효능감이 직무만족에 미치는 긍정적인 효과는 매우 높았지만, 성차별이 높은 집단에서는 업무효능감이 직무만족에 유의한 영향을 주지 않았다. 따라서 업무효능감이 직무만족에 미치는 영향은 성차별 수준에 의해 그 양상이 상당히 다르다는 사실이 입증되었다. 마지막으로, 성차별이 낮은 집단의 경우, 전문성이 직무만족에 직접적으로 유의한 영향을 미치지는 않았지만, 업무효능감을 완전매개로 하여, 전문성이 직무만족에 긍정적인 영향을 미칠 수 있음이 밝혀졌다. 즉, 업무효능감은 성차별이 적은 집단에서 전문성이 직무만족에 긍정적인 영향을 미칠 수 있게 하는 중요한 매개요인임이 입증되었다. 전문성이 직무만족에 미치는 영향에 업무효능감이 미칠 수 있는 매개효과, 그리고 업무효능감이 직무만족에 미치는 직접효과 등은 성차별 정도에 따라 유의하게 그 양상이 달라질 수 있음이 확인되어, 성차별의 조절효과가 실증적으로 규명되었다. 본 연구를 통해 밝혀진 주요 사실들을 토대로, 미디어 제작에 적극적으로 참여하고 있는 영상제작 인력들의 직무만족 수준을 높이기 위한 방안모색에 고려할 수 있는 실천적, 정책적 함의를 논의하였다. This study focuses on the situation that the importance of the film and television industry workers increases due to the expansion of video productions in various media areas. The predominant concern of the study consist of: (1) the direct effects of professionalism and career barrier on the job satisfaction of the film and television industry workers; (2) the mediating effect of the job efficacy on their job satisfaction; (3) the moderating effect of gender discrimination. The film and television industry workers have been overlooked in research despite of the active development in medai area. An empirical research was attempted, which is based on a survey conducted with 402 film and television workers who are in various fields(12) and positions(4). In order for respondents to verify research questions, structural equation models were explored. A variety of tests were conducted including multi-group analysis, and bias-corrected boot-strapping with AMOS 20. The notable findings are as follow: First, the professionalism of the film and television industry workers does not have direct effect on the job satisfaction, however, the career barrier influences on the job satisfaction in both group with higher and lower gender discrimination in wage, promotion, and job roles at work. Second, while the career barrier does not effect on the job efficacy, professionalism has a direct affect on the job efficacy in the both groups. Third, the job efficacy has a positive effect on the job satisfaction in the group with lower gender discrimination, but the effect of job efficacy is not significant in the group with higher gender discrimination. Therefore, the effect of job efficacy on job satisfaction is proved to be significantly different depending on the sex discrimination level. Lastly, while professionalism does not directly influence on the job satisfaction, it is found that professionalism can positively affect job satisfaction with full mediation effect of job efficacy in the group with lower gender discrimination. That is, job efficacy is proven to be an important mediator that has a positive effect on job satisfaction in a group with low gender discrimination. The moderating effect of gender discrimination is proved empirically according to the different tend between the two group in the direct and indirect effect of job efficacy on the job satisfaction. Some practical and political implications are discussed based on the study's findings in order to increase the job satisfaction of the film and television workers in media industry.